ANALGESIC ACTIVITY TEST OF SUJI LEAF ETHANOL EXTRACT (Dracaena angustifolia) IN MALE MICE (Mus musculus) ACCETIC ACID INDUCED - Deanser, Serli (Jurnal Farmasi Etam (JFE), 2023)
Suji Leaf (Dracaena angustifolia) or also known as the local name Suji Leaf plant that is widely spread and used for generations in Southeast Asia, including Indonesia. The purpose of this study was to determine the analgesic activity of the ethanolic extract of suji leaf which is efficacious as an analgesic in mice induced by 1% acetic acid. The results of the identification test of secondary metabolites of the ethanolic extract of suji leaves contain flavonoids, saponins, alkaloids, and steroids. Analgesic test using the chemical induction method of 1% acetic acid intra peritoneally in mice (Mus musculus) with 3 doses of ethanol extract of suji leaves. The results of the analgesic activity test of suji leaf extract successively at a dose of 25 mg/kgBW the analgesic power was 56.7%, at a dose of 50 mg/kgBW the analgesic power was 64.5%, at a dose of 100 mg/kgBW the analgesic power was 69.8%. Based on the ANOVA statistical test, there was a significant difference between the extract doses of 25 mg/kgBW, 50 mg/kgBB, 100 mg/kgBW to the positive control and the negative control 0.000 (ᴘ 0.05).